Central bank influence and housing financialisation: an empirical analysis on the case of Chile - Vergara-Perucich, Francisco (Bulletin of Geography. Socio-economic Series, 2026)
This article examines the role of Chile’s Central Bank in the financialisation of housing through an empirical analysis of the dynamic relationships between monetary policy, mortgage rates and real housing prices from 2004 to 2023. Employing a Vector Error Correction Model (VECM), the study identifies a long-run cointegrating relationship (HPI = –53.63 × Mortgage Rate + 16.23 × Policy Rate) in which housing prices are inversely related to mortgage rates but, counterintuitively, positively associated with the policy rate, suggesting speculative dynamics that complicate the central bank’s stabilising role. The model reveals that monetary policy transmits through mortgage markets with delayed and non-monotonic effects: contractionary shocks induce price declines peaking at 6 months, before reversing after 18 months. Crucially, forecast error variance decomposition shows that 98.9% of housing price fluctuations are driven by endogenous market dynamics, with monetary policy explaining only 0.4% of long-term variance. ...